Transformation of isochorismate synthase in tomato plants - Sidi, Siti Nurul Ain Binti (Universiti Malaysia Sarawak, UNIMAS, 2013)
Isochorismate synthase (ICS) is an important enzyme during the conversion of chorismate into isochorismate in the shikimate pathway. The cDNA was transformed into tomato plant to observe the functional and expression activity. The objective of this study is to insert the ICS gene isolated from Morinda citrifolia into tomato by seed via infiltration method. Mardi Tomato 1 (MT1) seeds were treated with sonication before immersed in infiltration broth on a shaking incubator and subsequently sown into soils. About 887 bp size of ICS cDNA was not successfully transformed into the MT1 plants confirmed by polymerase chain reaction (PCR).